Factors influencing farmers’ behavior towards modern rice varieties in Bangladesh - Islam, Mohammad Samiul; Kamarulzaman, Nitty Hirawaty; Shamsudin, Mad Nasir; Mohd Nawi, Nolila; Alam, Mohammad Jahangir; Bhandari, Humnath (HH Publisher, 2024)
The adoption of high-yielding agricultural technologies remains a promising strategy for achieving food security and poverty reduction in developing countries. With the innovation of green technology like seeds, fertilizers, and irrigation water, the productivity of land has increased significantly in Asian countries like Bangladesh. The high-yielding varieties of rice generate a yield gain of 15-20% over the conventionally bred varieties in general. Yet, despite strenuous government efforts, farmers’ adoption rates have remained low in Bangladesh compared to other Asian countries like India, China, and Vietnam. Therefore, this study was carried out to determine the factors influencing the adoption of modern high-yielding rice in some selected areas of the Mymensingh district in Bangladesh. A total of 510 smallholder rice farmers were randomly selected using a structured questionnaire. Descriptive analysis was used to evaluate the socio-demographic characteristics of farmers. The Tobit regression analysis was employed to figure out the factors influencing the adoption of modern rice cultivars. The results of the descriptive analysis showed that in the Boro season, about 64% of the area in the Mymensingh district was covered by modern high-yielding varieties. The outcome of Tobit regression indicated that variables such as farmers’ schooling, farm size, social membership, extension contract, training facilities, taste and preference, and yield capacity of new varieties were the significant and positive determinants to adopt modern rice cultivars, whereas farmers’ age, a distance of agricultural extension office, and fertilizer deficiency were significant but adversely associated with the adoption behaviour of the farmers. These findings recommended that rice breeders should emphasize the farmers’ preferences while developing varieties, as well as provide training, formal credit, trusted seed dealers, and membership access for spreading newly established HYV rice cultivars.